Vietnam : State, War, and Revolution (1945-1946) - Marr, David G. (Book collections on Project MUSE., 2013)
This book focuses on an era when Vietnam's course for the future was determined. The book recreates in detail what it was like to be there in these dramatic postcolonial moments as the Japanese, British, and Americans faded from view, the DRV began to function and establish an army, the French maneuvered to restore colonialism, but the beginnings of the Cold War swept Vietnam into its orbit with the Chinese Red Army victories and Chinese arms on the border. The author explores the history of war from the Vietnamese perspective.--adapted from publisher's description.